Capital and lowercase letters as a means of implementing the pragmatic potential of literary prose text - Sharshniova, Volha М. (Journal of the Belarusian State University. Philology, 2024)
The article examines and consistently describes the pragmatic meanings of capital and lowercase letters in literary prose text, namely the pragmatic meanings of individual words written with a capital letter; words written in capital letters; phrases and sentences written in capital letters; improper use of a lowercase letter instead of a capital one. It is argued that the implicit meanings of individual positions of such use may have the same or similar pragmatic potential, however, each of the noted positions is distinguished by its role as an additional means of transmitting thoughts and feelings, as an element of the structural and compositional organisation of the work, as a means of expressing perspective-retrospective relationships. It is concluded that the subjective perception of the pragmatic richness of the individual use of capital and lowercase letters motivates the writer to deviate from generally accepted rules, however, the author’s individuality does not lie in violating the norms of the spelling system, not in ignoring the traditional meanings of individual letters, but in strengthening their meaning as additional means transmission of thoughts and feelings in a literary text, in expanding the boundaries of their use.
Keywords: pragmatic potential; pragmatic functions; pragmatic meanings; literary text; prose text; capital letter; lowercase letter